PENGARUH PROMOSI DARI MULUT KE MULUT DAN KEPUASAN PELANGGAN TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR HONDA BEAT DI KOTA BEKASI - Chandra Dewi Pitaloka; Donny Dharmawan (Jurnal Ekonomi dan Industri, 2024)
The analyze the influence of word of mouth and customer satisfaction on the purchase decision of Honda Beat motorcycles in Bekasi City. The method of this research approach is a quantitative method with associative type. The population in this study is people in Bekasi City who already own or had ridden motorcycle with the Honda Beat Brand. Data collection with survey techniques through questionnaires, sampling techniques applying purposive sampling. The analysis method uses multiple and simple linear regression. The results of the research show that both multiple and simple word of mouth promotions and customer satisfaction have a positive and significant effect on purchasing decisions for Honda Beat motorbikes in Bekasi City.